In-work poverty dynamics: Trigger events and short-term trajectories in Argentina - Santiago Poy (Journal for Labour Market Research, 2023)
In-work poverty (IWP) is gaining interest in the public agenda. This article is a first contribution to the analysis of IWP dynamics in Latin America, based on the study of the Argentine case. Using one-year interval panel data, the paper analyzes the trigger events that produce entries and exits from IWP, short-term poverty trajectories and the determinants associated to transient and persistent poverty. Drawing on a decomposition analysis of mutually exclusive events, the article shows that labor market events are the most relevant triggers for both exits and entries into IWP. Based on a multinomial logistic regression, the paper concludes that low education, the presence of children in the household, and having a low-quality job are the three main factors explaining persistent-poverty.
Keywords: I32; E24; J62; C23; 330; s In-work poverty; Poverty dynamics; Labor market; Quality of employment